Five spice street - Canxue, 1953- (Margellos world republic of letters book., 2009)
"Five Spice Street tells the story of a street in an unnamed city, whose inhabitants speculate on the life of a mysterious Madam X. The novel interweaves their endless suppositions into a work that is at once political parable and surreal fantasia. Some think X is fifty years old, others that she is twenty-two. Some believe she uses occult powers to enslave the youth of the street; others think she is playing clever mind games with people. Who is Madam X? How has she brought the good people of Five Spice Street to their knees either in worship or in exasperation? The unknown narrator takes no sides in the endless interplay of visions, arguments, and opinions. The investigation rages as the street becomes a Walpurgisnacht of speculations, fantasies, and prejudices. Madam X is the vehicle through whom people bare their souls, reveal their innermost selves, even as they try to discover the mystery of her extraordinary powers." "Five Spice Street is an astonishing work of contemporary fiction. Exploring the collective consciousness of this little street of ordinary people, Can Xue penetrates the deepest existential anxieties of the present day - whether in China or in the West - where the impermanence of identity struggles with the narrative within which identity must compose itself."--Jacket